2022-RA-873-ESGO Validation study of the 'NOGGO-GIS ASSAY' based on ovarian cancer samples from the first-line PAOLA-1/ENGOT-ov25 phase-III trial. (20th October 2022) - Willing, Eva-Maria; Vollbrecht, Claudia; Voessing, Christine; Weist, Peggy; Schallenberg, Simon; Jori, Balazs; Tiemann, Markus; Bataillon, Guillaume; Harter, Philipp; Pignata, Sandro; Martin, Antonio Gonzales; Vergote, Ignace; et al.
Abstract : Introduction/Background: Several clinical trials have demonstrated that the maintenance with a PARP inhibitor with or without bevacizumab following platinum-based therapy improved PFS in advanced ovarian cancer patients. The benefit was significant greater in homologous recombination deficient (HRD) patients according to Myriad myChoice test. The PAOLA-1 olaparib+bevacizumab maintenance regimen was approved in USA/Europe/Japan for HRD and BRCA positive patients. Using sample from the PAOLA-1/ENGOT-ov25 we evaluated the novel 'NOGGO-GIS ASSAY' as part of the ENGOT HRD-European-Initiative. Methodology: A hybrid capture NGS assay based on the Agilent XTH2 chemistry and SNP backbone, was developed for the detection of somatic driver mutations in key cancer genes, BRCA1/2 mutations, HRR gene mutations and HRD in combination with a bioinformatic analysis pipeline based on publicly available tools. The assay was clinically validated using 468 ovarian cancer samples from the PAOLA-1/ENGOT-ov25 trial. Results: Here we report the first results of the 'NOGGO-GIS ASSAY' validation compared to the Myriad myChoice clinical trial. The assay is based on widely available hybrid capture chemistry, to cover 57 genes and approx. 20.000 SNP loci, automated for parallel processing of 48 samples per run and requires 50 ng of genomic DNA extracted from tissue section with at least 30% of tumor content with a low failure rate of around 5%. The performance characteristics of the NOGGO GIS Assay are comparable to the PAOLA-1/ENGOT-ov25 clinical trial assay. The NOGGO GIS Assay showed a similar impact of olaparib+bevacizumab on PFS with a comparable Hazard Ratio for HRD positive patients. Conclusion: The 'NOGGO-GIS ASSAY' based on widely available components was validated on clinical trial samples showing performance characteristics similar to the clinical trial assay. The low failure rate, low input material required, HRD and BRCA1/2 and mutation status in 57 clinically relevant genes makes this a highly attractive option for analysis of FFPE samples.